2017
DOI: 10.20343/teachlearninqu.5.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Helping University Students Succeed at Employment Interviews: The Role of Self-Reflection in e-Portfolios

Abstract: In the context of a Transition to Work course for fourth-year psychology majors, we had students use an e-portfolio to self-reflect on the learning experiences they deemed most significant during their degree. Such significant learning experiences can be drawn upon when answering behavioral job interview questions. We examined whether students would show improvement in mock behavioral interview performance over time, and whether any potential improvement was related to performance on self-reflective course ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Our data confirm other discipline-specific findings (Lackner & Martini, 2017) that students find co-curricular experiences to be among the most important learning experiences that they have during the course of their degree. This pattern of results provides some preliminary empirical support for Bass's (2012) assertion that the current cohort of postsecondary students finds greater value in co-curricular experiences than those that are connected to their classes.…”
Section: Importance Of Co-curricular Experiences and Feelings Of Prepsupporting
confidence: 90%
“…Our data confirm other discipline-specific findings (Lackner & Martini, 2017) that students find co-curricular experiences to be among the most important learning experiences that they have during the course of their degree. This pattern of results provides some preliminary empirical support for Bass's (2012) assertion that the current cohort of postsecondary students finds greater value in co-curricular experiences than those that are connected to their classes.…”
Section: Importance Of Co-curricular Experiences and Feelings Of Prepsupporting
confidence: 90%
“…Self-reflection differs from reflection, which was defined as the "mental process of structuring or restructuring an experience, a problem or pre-existing knowledge or existing recognition" [13] (p. 193). Self-reflection was found to have a positive impact on student performance [12,14,15] and heighten student self-efficacy and resilience [16].…”
Section: Self-reflection and Eportfoliosmentioning
confidence: 99%
“…Students are also becoming increasingly aware of the value of participating in activities outside of the classroom (Thompson et al, 2013). In research undertaken to explore student perceptions of learning experiences, when asked to outline eight of their most significant learning experiences, 52% of the experiences described were co-curricular (Lackner and Martini, 2017). Additionally, Clark et al (2015) found that, in the opinion of graduates, ECA significantly helped develop employability skills, contributed to their first employment, and enhanced their workplace performance, again demonstrating that there is a prevalent view amongst current students and graduates that ECA increases employability.…”
Section: Contextualising Employability and Higher Education In The Ukmentioning
confidence: 99%